Consumer protection in e-Commerce transactions: A study in Iraqi legislations / Ibraheem Hammood Mhana - Ibraheem Hammood , Mhana (2018)
Due to the growing number of Internet users and the development of e-commerce transactions worldwide, the concept of e-consumer protection has become more necessary, and has received much attention, because the consumer in e-commerce transactions is the weak party and is often cheated. However, the legal legislation, at the national and international levels, did not provide adequate protection, even though the online contractual relationship is a transboundary relationship and often involve an international party. This thesis aims to examine consumer protection legislation in Iraq to demonstrate the provided legal protection to the consumer in e-commerce. The significance of this study appears in the light of the issuance of the Iraqi Consumer Protection Act No. 1 of 2010, as the Act did not stipulate any kind of consumer protection for online transactions. The Electronic Signature and Electronic Transactions Act No. 78 of 2012 is also exempt from any provision relating to electronic consumer protection. This research applies the comparative analytical methodology. The comparison is made between the Iraqi acts and acts from countries such as France, Egypt. The findings reveal that both, the Iraqi Consumer Act and The Electronic Signature and Electronic Transactions Act, do not provide adequate and effective protection to the consumer as they do not address, fully or partially, many issues relating to consumer protection. These issues include the unfair terms, the right to access information about the goods, service or the provider. These issues include the unfair terms, the right to access information about the goods, service or the provider. The acts also do not address the legal protection for e-consumer in case of hijacking data and documents shared online. Overlooking such crucial issues is a deficiency that the Iraqi legislature should redress.